Antitumor activity of pan‐HER inhibitors in HER2‐positive gastric cancer. Issue 4 (25th March 2018) - Yoshioka, Takahiro; Shien, Kazuhiko; Namba, Kei; Torigoe, Hidejiro; Sato, Hiroki; Tomida, Shuta; Yamamoto, Hiromasa; Asano, Hiroaki; Soh, Junichi; Tsukuda, Kazunori; Nagasaka, Takeshi; Fujiwara, Toshiyoshi; et al.
Abstract : Molecularly targeted therapy has enabled outstanding advances in cancer treatment. Whereas various anti‐human epidermal growth factor receptor 2 (HER2) drugs have been developed, trastuzumab is still the only anti‐HER2 drug presently available for gastric cancer. In this study, we propose novel treatment options for patients with HER2‐positive gastric cancer. First, we determined the molecular profiles of 12 gastric cancer cell lines, and examined the antitumor effect of the pan‐HER inhibitors afatinib and neratinib in those cell lines. Additionally, we analyzed HER2 alteration in 123 primary gastric cancers resected from Japanese patients to clarify possible candidates with the potential to respond to these drugs. In the drug sensitivity analysis, both afatinib and neratinib produced an antitumor effect in most of the HER2 ‐amplified cell lines. However, some cells were not sensitive to the drugs. When the molecular profiles of the cells were compared based on the drug sensitivities, we found that cancer cells with lower mRNA expression levels of IGFBP7, a tumor suppressor gene that inhibits the activation of insulin‐like growth factor‐1 receptor (IGF‐1R), were less sensitive to pan‐HER inhibitors. A combination therapy consisting of pan‐HER inhibitors and an IGF‐1R inhibitor, picropodophyllin, showed a notable synergistic effect. Among 123 clinical samples, we found 19 cases of HER2 amplification and three cases of oncogenic mutations. In conclusion, afatinib and neratinib are promising therapeutic options for the treatment of HER2 ‐amplified gastric cancer. In addition to HER2 amplification, IGFBP7 might be a biomarker of sensitivity to these drugs, and IGF‐1R ‐targeting therapy can overcome drug insensitiveness in HER2 ‐amplified gastric cancer. Abstract : Currently, trastuzumab is the only anti‐HER2 drug for HER2‐positive gastric cancer, whereas various anti‐HER2 drugs have been developed. In this study, we showed a potent anti‐tumor effect of the pan‐HER inhibitors afatinib and neratinib against HER2‐amplified gastric cancer cells both in vitro and in vivo. Pan‐HER inhibitors could be a promising treatment option for HER2‐positive gastric cancer patients.